Pharmacological and non-pharmacological treatments for restless legs syndrome in end-stage kidney disease: a systematic review and component network meta-analysis. Issue 10 (6th October 2021) - Chen, Jia-Jin; Lee, Tao Han; Tu, Yu-Kang; Kuo, George; Yang, Huang-Yu; Yen, Chieh-Li; Fan, Pei-Chun; Chang, Chih-Hsiang
ABSTRACT: Background: Restless legs syndrome (RLS) is common among patients with end-stage kidney disease (ESKD) and is associated with poor outcomes. Several recently published studies had focused on pharmacological and non-pharmacological treatments of RLS, but an updated meta-analysis has not been conducted. Methods: The study population was adult ESKD patients on dialysis with RLS. Randomized controlled trials (RCTs) were selected. The primary outcome was reduction in RLS severity. The secondary outcomes were improvement in sleep quality and treatment-related adverse events. Frequentist standard network meta-analysis (NMA) and additive component NMA were performed. The evidence certainty was assessed using the Confidence in NMA (CINeMA) framework. Results: A total of 24 RCTs with 1252 participants were enrolled and 14 interventions were compared. Cool dialysate produced the largest RLS severity score reduction {mean difference [MD] 16.82 [95% confidence interval (CI) 10.635–23.02]} and a high level of confidence. Other potential non-pharmacological interventions include intradialytic stretching exercise [MD 12.00 (95% CI 7.04–16.97)] and aromatherapy massage [MD 10.91 (95% CI 6.96–14.85)], but all with limited confidence of evidence. Among the pharmacological interventions, gabapentin was the most effective [MD 8.95 (95% CI 1.95–15.85)], which also improved sleep quality [standardized MD 2.00 (95% CI 0.47–3.53)]. No statically significant adverse events were detected. Conclusions: The NMA supports that cool dialysate is appropriate to treat patients with ESKD and RLS. Gabapentin is the most effective pharmacological intervention and also might improve sleep quality. Further parallel RCTs with sufficient sample sizes are required to evaluate these potential interventions and long-term effects. Graphical Abstract: